Cassava breeding: current status, bottlenecks and the potential of biotechnology tools - Ceballos, Hernán; Kulakow, Peter A.; Hershey, Clair H. (Springer, 2012)
Cassava is an important energy source in the diets of millions of people in tropical and subtropical regions of the world. It is a key subsistence crop, and its industrial uses are steadily growing. In spite of its economic and social relevance, relatively little investment has been made for research on cassava. However, conventional breeding resulted in more stable production through enhanced tolerance to biotic and abiotic stresses; increased productivity, both in fresh root production and increased dry matter content; and, more recently, improvements in qualitative traits such as starch quality and increased carotenoids content. The inbreeding of cassava has been identified as a key step for more efficient genetic improvement of the crop, therefore, research is underway to develop protocol(s) for the production of doubled haploids. Marker-assisted selection has been successfully applied to cassava, but in a more modest scale compared with other crops. More support and emphasis is needed on practical applications of molecular marker technology in cassava improvement. The availability of more efficient genotyping approaches and the cassava genome sequence promise to increase the impact of biotechnology tools on cassava improvement. Efficient and reliable phenotyping of cassava remains a challenging goal to achieve in the near future.